1994
DOI: 10.2116/analsci.10.615
|View full text |Cite
|
Sign up to set email alerts
|

Flow-through Type Chloride Ion Selective Optodes Based on Lipophilic Organometallic Chloride Adducts and a Lipophilic Anionic Dye

Abstract: Flow-through type fiber-optic chloride ion selective optodes have been developed based on chloride adducts of lipophilic organometallic compounds, including a metal: Sn, Ge, Hg or Hf and a lipophilic anionic indicator dye of the Biphenyl amine type. The pellicular-type ODS beads were coated with a lipophilic organic liquid containing the lipophilic organometallic compound as the anion-selective ionophore ligand and LAD-3 as the color changeable indicator dye. The optode system was constructed by packing these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…As compared to corresponding ISEs, optodes with trioctyltin chloride as an ionophore give a much better stability and a faster response. , The use of this optode for the determination of Cl - in human plasma was demonstrated and it was shown that SCN - did not interfere significantly at concentrations typically occurring in samples from smokers (trioctyltin chloride, log (SSM): ClO 4 - , −0.7; NO 3 - , −1.8; Br - , +0.3; SO 4 2- , −2.8; SCN - , +1.1; I - , +1.0; ETH 7075 ( H + -12 ), BBPA). A similar selectivity was also found for tricyclohexyltin chloride ( Cl - -9 ), which under otherwise identical conditions seems to allow lower detection limits than tributyltin and trioctyltin chloride, while optodes based on triphenylgermanium chloride ( Cl - -10 ) and phenylmercuric chloride ( Cl - -11 ) as well as hafnocene dichloride ( CA - -2 ; for use of this ionophore see also “Sensors for Carboxylates”, section IV.3) only weakly respond to Cl - . , A better discrimination of several interfering ions was found for optodes with chloro(octaethylporphyrinato)indium(III) ( Cl - -4 ) and either ETH 2412 ( H + -40 ) or fluorescein as chromoionophore (log (SSM): ClO 4 - , −2.2; NO 3 - , −2.8; Br - , +0.1; I - , +0.2; SCN - , −1.8; ETH 2412, oNPOE, PVC and Tecoflex polyurethane matrix; pH 4.2) …”
Section: Cl- Sensorsmentioning
confidence: 54%
See 2 more Smart Citations
“…As compared to corresponding ISEs, optodes with trioctyltin chloride as an ionophore give a much better stability and a faster response. , The use of this optode for the determination of Cl - in human plasma was demonstrated and it was shown that SCN - did not interfere significantly at concentrations typically occurring in samples from smokers (trioctyltin chloride, log (SSM): ClO 4 - , −0.7; NO 3 - , −1.8; Br - , +0.3; SO 4 2- , −2.8; SCN - , +1.1; I - , +1.0; ETH 7075 ( H + -12 ), BBPA). A similar selectivity was also found for tricyclohexyltin chloride ( Cl - -9 ), which under otherwise identical conditions seems to allow lower detection limits than tributyltin and trioctyltin chloride, while optodes based on triphenylgermanium chloride ( Cl - -10 ) and phenylmercuric chloride ( Cl - -11 ) as well as hafnocene dichloride ( CA - -2 ; for use of this ionophore see also “Sensors for Carboxylates”, section IV.3) only weakly respond to Cl - . , A better discrimination of several interfering ions was found for optodes with chloro(octaethylporphyrinato)indium(III) ( Cl - -4 ) and either ETH 2412 ( H + -40 ) or fluorescein as chromoionophore (log (SSM): ClO 4 - , −2.2; NO 3 - , −2.8; Br - , +0.1; I - , +0.2; SCN - , −1.8; ETH 2412, oNPOE, PVC and Tecoflex polyurethane matrix; pH 4.2) …”
Section: Cl- Sensorsmentioning
confidence: 54%
“…The use of a tetraphenylborate salt of Capriquat with impurities (Capriquat is known to contain besides trioctylmethylammonium chloride several other tetraalkylammonium salts) or a carrier concentration effect may be responsible for the fairly different selectivities found with coated wire electrodes (trioctyltin chloride, log (SSM): NO 3 - , 0.0; Br - , +0.4; I - , ≥5.0; SCN - , +3.0; OAc - , −0.9; SO 4 2- , −2.1; tetraphenylborate salt of Capriquat, 1-octadecanol, triphenyl phosphate) was not very successful when used in later studies, ,, probably because of the low stability of the complex of Cl - and triphenyltin chloride …”
Section: Cl- Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrodes using metalloporphyrin as ionophore usually show a super-Nernstian response, and a large potential change occurs within a narrow concentration range that is generated by forming a dimeric metalloporphyrin structure (39)(40)(41). This type of metalloporphyrin has also been applied to develop optical sensors for anions (42)(43)(44) and neutral species (45) based on spectrometry and fluorescence methods. The Schiff-base complexes of Co (II) (46) or Ce (III) (47) (I-6) were also used in preparing the highly selective iodide membrane electrodes.…”
Section: Ionophore-based Iodide-ises For Ui Assaymentioning
confidence: 99%
“…Many kinds of ion-selective optodes for various analytes have been reported, such as Li + , 1 Na + , 2 K + , [3][4][5] NH 4 + , 6,7 Mg 2+ , 8 Ca 2+ , [8][9][10][11][12] Zn 2+ , 13 Ag + , 14,15 Hg 2+ , 14 UO 2 2+ , 16 Pb 2+ , 17 HSO 3 -, 18 Cl -, 19,20 , and heparin; 21 their theoretical methodologies have also been investigated. 1,3,11,22,23 In the field of dry reagent chemistry, simple chemical sensing probes such as protein and sugar test papers were developed.…”
mentioning
confidence: 99%